Nieetyczne zachowania ubezpieczonych na polskim rynku ubezpieczeń - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2012)
For many years we have observed the occurrence of extorting compensation from insurance companies. The scale of it is not fully identified. Despite the enormous effort to combat with this phenomenon, the size of it is still growing. The article discusses the reasons for this phenomenon, especially motivation and tendency of the insured to fraud. It also presents the economic consequences of the phenomenon for insurance companies.